SOCIAL CONFLICT IN THE NOVEL SI ANAK PEMBERANI BY TERE LIYE: STUDI SOCIAL CONFLICT LEWIS A. COSER - Anggreni, Wika; Abidin, Aslan; Satriani, Irma (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2025)
This study aims to describe the forms of social conflict found in novel Si Anak Pemberani by Tere Liye's based on Lewis A. Coser's theory of social conflict using a literary sociology approach. The type of research used is descriptive qualitative research, which aims to interpret data in the form of social conflict discourse that appears in the novel text. The source of data for this research is the novel Si Anak Pemberani by Tere Liye. Data collection techniques were carried out by reading and taking notes. Data analysis was carried out through the stages of identification, classification, interpretation, and conclusion drawing. The results of the study show that in this novel there are two forms of social conflict, namely realistic conflict and non-realistic conflict. Realistic conflict arises due to concrete social needs and demands such as livelihood, justice, equality, and environmental sustainability directed at those in power, officials, and mining companies as the source of the problem. Meanwhile, non-realistic conflict arises as a form of emotional venting, such as anger, disappointment, or frustration, which has no clear purpose and is often directed at parties who are made scapegoats. Overall, these two forms of conflict describe the social reality of a society fraught with tension and the struggle against injustice